Outcomes using the T-14 symptom score for tonsillectomy in an Australian paediatric population - Lam, Matthew Eugene; Woods, Charmaine M.; Du, Charles; Milton, Thomas; Kao, Stephen Shih-Teng; Huynh, Julie; Sigston, Elizabeth; Ooi, Eng H. (Australian Journal of Otolaryngology; Vol 2 (January 2019): Australian Journal of Otolaryngology, 2019)
Background: Quality of life (QoL) outcomes afterpaediatric tonsillectomy can be assessed with disease-specific patient reportedoutcome measures. Our aim was to assess a modified T-14 Paediatric ThroatDisorders Outcome Test in an Australian paediatric population undergoing tonsillectomy. Methods: A consecutive case series wasconducted in children (aged 1–16 years) undergoing tonsillectomy over a periodof 15 months. T-14 questionnaires administered to the caregivers of the childpre-operatively and post-operatively (n=45) within 6–8 weeks of the procedurewere included for statistical analysis. Pre- and post-operative T-14 scoreswere compared and analysed according to surgical indication [either sleepdisordered breathing (SDB), recurrent tonsillitis, or both] and complicationswith non-parametric tests. Results: Post-operative scores demonstrated aglobal improvement for SDB (n=22), recurrent tonsillitis (n=12) and for both(n=11) indications (P